2020
DOI: 10.32468/be.1135
|View full text |Cite
|
Sign up to set email alerts
|

Misallocation of the Immigrant Workforce: Aggregate Productivity Effects for the Host Country

Abstract: Mass migrations can impact the amount of labor misallocation in the host country if immigrants, relative to natives, face more frictions that prevent them from working in their preferred occupations. The resulting misallocation would imply an aggregate productivity loss in the short run while migration occurs, but an subsequent lapse of productivity growth when the immigrants start to be assimilated by the labor market. We study the case of Colombia during 2015-2019, a period when the country received a massiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Studies have been conducted on the overeducation of Venezuelan immigrants, mainly in Colombia and Peru, because these are the countries with the highest Venezuelan immigration (R4V, 2022). In Colombia, several authors found the presence of overeducation of Venezuelan immigrants for different reasons, such as labor discrimination (Pulido & Varón, 2020); the years of residence (Lebow, 2022;Mora, Cuadros-Menaca, et al, 2022); the migratory situation, and the sociodemographic characteristics of the Venezuelan region of origin (Mora, Castillo Caicedo, et al, 2022); and the costs and long waits to validate past educational credentials (Santamaria, 2022). In Peru, the Venezuelan migration has intensified recently mostly in 2018 (Asencios & Castellares, 2020), then, Vera & Jiménez (2022) found a degree of imperfect substitutability through statistical analysis between Venezuelan immigrants and Peruvians…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies have been conducted on the overeducation of Venezuelan immigrants, mainly in Colombia and Peru, because these are the countries with the highest Venezuelan immigration (R4V, 2022). In Colombia, several authors found the presence of overeducation of Venezuelan immigrants for different reasons, such as labor discrimination (Pulido & Varón, 2020); the years of residence (Lebow, 2022;Mora, Cuadros-Menaca, et al, 2022); the migratory situation, and the sociodemographic characteristics of the Venezuelan region of origin (Mora, Castillo Caicedo, et al, 2022); and the costs and long waits to validate past educational credentials (Santamaria, 2022). In Peru, the Venezuelan migration has intensified recently mostly in 2018 (Asencios & Castellares, 2020), then, Vera & Jiménez (2022) found a degree of imperfect substitutability through statistical analysis between Venezuelan immigrants and Peruvians…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Yet, more than 70% of them were employed in the informal labor market. This produced a significant misallocation of migrant workers, as most of them were working in occupations that did not match their qualifications (Lebow, 2024;Pulido and Varón, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this paper contributes to the literature on the interplay between migrant downgrading and productivity. While previous works have primarily focused on the potential productivity gains from reallocating downgraded migrants to occupations that match their qualifications (Lebow, 2024;Pulido and Varón, 2023), This study introduces a distinct perspective. It argues that downgrading and misallocation do not necessarily translate into a negative effect on productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Pulido and Varon (2020) also discusses the implications for the evolution of the labor force and unemployment in the future.IMF DEPARTMENTAL PAPERS • Regional Spillovers from the Venezuelan Crisis…”
mentioning
confidence: 99%